Pertunjukan Wayang Orang-Orangan sebagai Upaya Pelestarian Bahasa Tegalan - Alfina, Zulfah; Naam, Muh. Fakhrihun; Sugiarto, Eko (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Wayang Orang-Orangan, a unique blend of traditional Indonesian performing arts and modern innovation, is a powerful tool for preserving cultural heritage. This traditional art form originating from Tegal, Indonesia, combines elements of wayang golek, music and dance to create a captivating performance that showcases a rich cultural heritage. Through its fusion of traditional and modern elements, Wayang Orang-Orangan has successfully captured the attention of a new generation of Indonesians, promoting a sense of identity and cultural pride. This article highlights the importance of Wayang Orang-Orangan as a means to preserve cultural heritage, especially the use of Tegal language in the face of globalization and modernization. By embracing innovation and adaptation, this traditional art form has managed to remain relevant, educating and entertaining audiences about the importance of preserving cultural identity.